2012
DOI: 10.4103/1817-1745.106474
|View full text |Cite
|
Sign up to set email alerts
|

Acalvaria: A rare congenital malformation

Abstract: Acalvaria is described as a rare congenital malformation in a 1-month-old female baby who presented with classical clinical features of soft, lax skull as a result of absent skull bones and associated muscles. Acalvaria is usually a fatal anomaly and is rarely discussed in English literature. Thus, we herein report a living case of acalvaria along with a review of the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 6 publications
1
16
0
1
Order By: Relevance
“…Some authors have reported success with conservative nonsurgical management. 2,5 However, the children in these cases had scalp overlying their skull defect, providing protection from meningeal infection. The child featured in the present report lacked scalp and skull, leaving a thin dural layer exposed to the outside elements and prone to physical damage and infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have reported success with conservative nonsurgical management. 2,5 However, the children in these cases had scalp overlying their skull defect, providing protection from meningeal infection. The child featured in the present report lacked scalp and skull, leaving a thin dural layer exposed to the outside elements and prone to physical damage and infection.…”
Section: Discussionmentioning
confidence: 99%
“…2,3,5,6 Although its etiology is not clear, it is postulated to represent a postneurulation defect. The disorder is usually fatal and may be associated with other abnormalities.…”
mentioning
confidence: 99%
“…1 Although the basal and facial bones are normally developed, the cranial content can often be abnormal. [1][2][3] Its pathogenesis is not well known, but the abnormality occurring after neurulation is the most accepted theory. [1][2][3] It is a fatal condition with only a few cases of survivors often with severe neurological disorders.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Its pathogenesis is not well known, but the abnormality occurring after neurulation is the most accepted theory. [1][2][3] It is a fatal condition with only a few cases of survivors often with severe neurological disorders. [1][2][3][4] To date, only one case has been reported in Africa.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation